Refining the rat sciatic nerve block: a novel ultrasound-guided technique. (April 2022) - Hughey, Scott; Campbell, Donald; Rapp-Santos, Kamala; Cole, Jacob; Booth, Gregory; Longwell, Jason; Stedje-Larsen, Eric
Murine translational models are an important tool to understand pain pathophysiology. One procedure used frequently in murine research is the sciatic nerve block. This study sought to demonstrate the use of ultrasound-guided sciatic nerve block in a cadaveric murine model. A total of 40 injections were performed in 20 Sprague–Dawley male 18-month-old rat cadavers. Necropsy was performed to identify staining of the sciatic nerve. Staining with methylene blue occurred in 40 of 40 ultrasound-guided injections. The extremely accurate nature of this block under ultrasound guidance is favorable for future translational studies in rats undergoing sciatic nerve blocks. This method may represent a significant improvement in current methods.